Gurre Kamilaroi, : or, Kamilaroi Sayings (1856) - Ridley, William, 1819-1878; Mason, Walter George, 1820-1866 (Salt Lake City, UT : Project Gutenberg, 2005)
"Gurre Kamilaroi, by William Ridley" is a linguistic and cultural publication written in the mid-19th century. This book serves as a guide to the Kamilaroi language, which is spoken by Indigenous Australians along the Namoi River and surrounding areas. Its primary focus is on providing insights into the language, alongside attempts to communicate Christian teachings to Aboriginal communities in that region. The content of "Gurre Kamilaroi" consists of a structured presentation of the Kamilaroi language, including vocabulary, pronunciation rules, and fundamental phrases. It incorporates Christian narratives, highlighting key stories such as the creation of man and woman, the life of Jesus (referred to as Immanuel), and his miracles, such as raising Lazarus from the dead. The book aims to teach readers the basics of the Kamilaroi language while sharing important spiritual messages, ultimately advocating for the education of Aboriginal people in their language and the Christian faith. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Gurre_kamilaroi
Release date is 2005-10-07
Keywords: Kamilaroi language -- Terms and phrases; Kamilaroi language -- Readers